Antagonistic Microbe on Palm Soil for Producing of Plant Growth Promoting Rhizobacteria Yeast and Fungal (PGPR) Mixed Microbe - Rattanaloeadnusorn, Sukhan (Recent Science and Technology, 2020)
Isolation of microorganisms on soil samples after using PGPR analysis of the 1,500-bp nucleotide sequence of the 16S rRNA gene by using the BLASTN program was compared with NCBI's GenBank data with a confidence level more than 99-100 percent. Morphogical characteristics and biochemical characterization taking place at Nong Suea District, Pathum Thani Province, Thailand found 14 isolates of microorganisms: actinomyces is Streptomyces themodiastatics, Fungal 7 isolates: Aspergillus terreus, Aspergillus fumgatus, Aspergillus tamari, Penicillium pennosus, Rhizomucor pusilus and Trichoderma asperelium Bacteria 5 isolates: Bacillus velezensis, Lactobacillus pentosus, Bacillus subtilis, Bacillus flexus and Bacillus lichenifermis: 1 isolates of yeast: Sacharomyces cerevisiac. The PGPR according to the method of Rattanaloeadnusorn (2517), and after the innovative PGPR sowing to sow under palm oil weight of 1 and 2 kg per 3 times per year. For 3 and 5 years old palm trees, it was found that the percentage increasing of palm kernel weight gain after using PGPR was 128.57±1.0% and 123.23±1.0% respectively. Results showed that the microorganisms in the bioproducts accelerated the digestion of nutrients into small molecule compounds and slowly released nutrients to plant roots. Palm oil farmers should turn to the innovative PGPR accelerating the growth, weight increase palm kernel, and weight gain per acre per year.